Fetal Cytomegalovirus Associated Intraventricular Hemorrhage: A Rare Prenatal Complication - Tang, Vincent D.; Heibig, Jennifer; Quiñones Rivera, Joanne N.; Sarno, Albert P.; Rochon, Meredith (American Journal of Perinatology Reports, 2025)
Intraventricular hemorrhage (IVH) is an uncommon manifestation of congenital cytomegalovirus (CMV) infection. We report a case of primary CMV infection associated with preterm labor as well as fetal anemia, thrombocytopenia, and IVH. The finding of unexplained IVH on ultrasound provided an indication for testing of congenital infection. Our case indicates the need for detailed sonographic imaging in pregnancies complicated by preterm labor, as the integration of ultrasound diagnosis can significantly impact management and improve perinatal outcomes.
Keywords: cytomegalovirus; intraventricular hemorrhage; fetal ultrasound; prenatal diagnosis; congenital infection